Grace and Agency in Paul and Second Temple Judaism interpreting the transformation of the heart - Wells, Kyle B. 1980- (Leiden Boston Brill, 2015)
Following recent intertextual studies, Wells examines how descriptions of 'heart-transformation' in Deut 30, Jer 31-32 and Ezek 36 influenced Paul and his contemporaries' articulations about grace and agency.
Intro -- Contents -- Acknowledgements -- Chapter 1 Introduction -- 1.1 Paul, Grace, and Agency -- 1.2 Method of Investigation -- Part 1 Jewish Scriptures: Restoration Agency in Deuteronomy, Jeremiah, and Ezekiel -- Chapter 2 Deuteronomy 30: God and Israel in the Drama of Restoration -- 2.1 Reading 1: The Priority of Israel in Restoration -- 2.2 Reading 2: Divine Priority in Restoration -- 2.3 Conclusion -- Chapter 3 Heart Transformation in the Prophets:Jeremiah and Ezekiel -- 3.1 The Heart and Its Transformation in the Book of Jeremiah -- 3.2 Ezekiel and the Recreation of Moral Agents -- 3.3 Conclusion -- Part 2 Early Jewish Interpretation and Theology -- Chapter 4 The Septuagint -- 4.1 Introduction -- 4.2 Initiative and Agency -- 4.3 Heart Operation -- 4.4 Conclusion -- Chapter 5 The Dead Sea Scrolls -- 5.1 Introduction -- 5.2 Scriptural Engagement -- 5.3 The Sectarian Community: Larger Considerations -- 5.4 Summary and Conclusions -- Chapter 6 The Apocrypha and Pseudepigrapha -- 6.1 Baruch -- 6.2 Jubilees -- 6.3 Second Baruch -- 6.4 Fourth Ezra -- 6.5 Summary and Conclusion -- Chapter 7 Philo -- 7.1 Introduction -- 7.2 Deuteronomy 30 and Restoration -- 7.3 Philo and Heart-Circumcision -- 7.4 Conclusion -- Part 3 Paul -- Chapter 8 Paul's Reading of Deuteronomy 30 in Romans 2:17-29 -- 8.1 Introduction: Establishing the Connection -- 8.2 The Way to Life and Fulfilling the Commands -- 8.3 Heart-Circumcision and the Reconstitution of the Moral Agent -- 8.4 Conclusion -- Chapter 9 Paul's Reading of Restoration:Further Considerations -- 9.1 Romans 7:5-6: A Critical Link -- 9.2 Moral Agents in Eschatological Contrast -- 9.3 Life in the Flesh: Moral Agents in the Old Aeon -- 9.4 New Creation: The Reconstitution of the Human Agent in Christ -- 9.5 Summary and Conclusions -- Chapter 10 Paul's Reading of Restoration Outside Romans.
Part 2 Early Jewish Interpretation and TheologyChapter 4 The Septuagint; 4.1 Introduction; 4.2 Initiative and Agency; 4.3 Heart Operation; 4.4 Conclusion; Chapter 5 The Dead Sea Scrolls; 5.1 Introduction; 5.2 Scriptural Engagement; 5.3 The Sectarian Community: Larger Considerations; 5.4 Summary and Conclusions; Chapter 6 The Apocrypha and Pseudepigrapha; 6.1 Baruch; 6.2 Jubilees; 6.3 Second Baruch; 6.4 Fourth Ezra; 6.5 Summary and Conclusion; Chapter 7 Philo; 7.1 Introduction; 7.2 Deuteronomy 30 and Restoration; 7.3 Philo and Heart-Circumcision; 7.4 Conclusion; Part 3 Paul
Description based on publisher supplied metadata and other sources
Keywords: Bible -- Versions -- Septuagint; Dead Sea Scrolls -- Criticism, interpretation, etc; Dead Sea Scrolls -- Relation to the Old Testament; Bible -- Theology; Bible -- Relation to the Old Testament; Bible -- Criticism, interpretation, etc; Grace (Theology) -- Biblical teaching; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Bible ; Epistles of Paul ; Criticism, interpretation, etc; Bible ; Epistles of Paul ; Relation to the Old Testament; Grace (Theology) ; Biblical teaching; Paul ; the Apostle, Saint ; Theology; Hochschulschrift